The Influence of Management Accounting Systems on Manufacturing Company Performance in Indonesia - Ulfah, Almira Keumala; Ramadhan, Ramadhan; Nadilla, Trie; Nasution, Muhammad Syafril; Hardjito, Awis (Jurnal Akuntansi Muhammadiyah (JAM), 2025)
This study aims to analyze the influence of management accounting systems (MAS) on the performance of manufacturing companies in Indonesia. In the context of global competition and the increasingly complex dynamics of the manufacturing industry, the existence of MAS is crucial because it provides relevant, accurate, and timely information for managers in strategic and operational decision-making processes. Company performance in this study is measured through two main dimensions: financial aspects (cost efficiency and profitability) and non-financial aspects (product innovation, customer satisfaction, and production quality). The research method uses a quantitative approach with data collection through a survey of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The data obtained were analyzed using multiple linear regression to examine the relationship between independent and dependent variables. The results show that the implementation of MAS has a positive and significant impact on the performance of manufacturing companies. Effective implementation of MAS has been proven to increase production cost efficiency, improve internal control, and encourage increased company competitiveness in the market. These findings emphasize the strategic role of MAS not only as a recording tool, but also as a managerial instrument that supports the sustainability and growth of companies in the era of digitalization and global competition. This research provides practical implications for company management to continue optimizing the use of MAS, so that the information produced can be more relevant, timely, and useful in supporting strategic decision-making oriented towards improving long-term performance.